A −40–125 °C, 0.8 V, 33 kHz relaxation oscillator with integrated voltage and current reference and compensated comparator delay. (November 2021) - Wang, Lidan; Zhan, Chenchang; Zhang, Zhaobo; Zhao, Shuangxing
Abstract: This paper presents a novel 33 kHz relaxation oscillator with temperature compensation over −40–125 °C range. The voltage and current references are integrated within the proposed relaxation oscillator, and the resistor used to generate the voltage reference can be omitted. The reference voltage for the comparator input is temperature insensitive, and the temperature coefficient (TC) of the bias current is utilized to compensate the TC of the comparator delay. The proposed oscillator with integrated voltage and current reference and compensated comparator delay is fabricated in a 180-nm CMOS process with an active area of 0.057 mm 2 . The measured average TC of the output frequency is 96.1 ppm/°C for a temperature range of −40–125 °C, and the line sensitivity is 2.6%/V for supply voltage of 0.8–2V. The power consumption is 97 nW when the supply voltage is 0.8V, and the frequency variation is ±0.7%.